The Impact of Energy Intensity on Environmental Inequity - Ziyi Xu (Journal of World Economy, 2023)
With the determination of carbon neutrality target, energy structure has become an important indicator to measure regional pollution emissions. In order to study the impact of energy intensity on environmental inequity, this paper uses threshold model to study the impact of energy intensity change on environmental inequity based on the panel data of 30 provinces from 2000 to 2020.The results show that there is a non-linear U-shaped relationship between energy intensity and environmental inequity. With the increase of energy intensity, the impact of energy intensity on environmental inequity does not play the role of mitigation, but more significantly aggravates the degree of environmental inequity.